Hypothèses sur l’évolution de la végétation littorale des Petites Antilles depuis l'époque précolombienne : le cas de la Martinique - Philippe Joseph (Cybergeo, 2006)
In the mountainous islands of Lesser Antilles, the climatic gradients, provided from the geomorphological patterns identify a complex vegetal building, clearly noticeable throughout the physiognomies and within the landscapes expressed by the great floristic unities, as well. The latter, from the margin to the summits, where the sylvatic ecosystems can develop, have potential: tropical seasonal Sempervirente (lower and middle floors), tropical submontane rainbow and tropical montane rainbow (upper level). The lower stage, where the populations of the first large plantations developed, has suffered a severe ecosystem degradation. The original equilibrium being broken due to anthropization in this dry bioclimate area, the regression process resulted in the establishment of vegetation (in particular littoral) of variable xericity, mainly composed of herbaceous, shrub and presylvatics. Forest formations are rare, secondary and low-biodiversity. However, within the coastlines of this archipelagic system, there are marginally advanced or subclimatic units of organization, similar to primitive referents. It was in the light of the data generated by the study of these relictual plant entities that it was possible to reconstitute the vegetal carpet of the pre-Columbian coastline and to understand the multiple modalities of the plant succession as well as the associated factorial constraints.